2013
DOI: 10.1016/j.janxdis.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of attachment relationships and peer relationship dysfunction among late adolescents with and without anxiety disorders

Abstract: Little is known about the links between anxiety disorders and parent-child attachment disorganization and quality of peer relationships in late adolescence. This study examined the quality of attachment and peer relationships among adolescents with and without anxiety disorders in a sample of 109 low-to moderate-income families. Psychopathology was assessed with the SCID-I. Attachment disorganization and dysfunction in peer relationships were measured using semi-structured interviews and behavioral observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
2
18
0
2
Order By: Relevance
“…This is consistent with findings between attachment and social anxiety in children and adolescents (i.e. Brumariu & Kerns, 2008;Brumariu, et al, 2013). However, when both attachment anxiety and avoidance are high, as in fearful attachment styles, an even stronger association with social anxiety was observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with findings between attachment and social anxiety in children and adolescents (i.e. Brumariu & Kerns, 2008;Brumariu, et al, 2013). However, when both attachment anxiety and avoidance are high, as in fearful attachment styles, an even stronger association with social anxiety was observed.…”
Section: Discussionsupporting
confidence: 91%
“…Vertue (2003) posits a unifying theory linking evolutionary, self-presentation and learning theories of social anxiety through the lens of attachment to explain the origins, development and maintenance of social anxiety. Vertue's hypothesises that early life experiences can result in IWMs of self as inferior, undesirable, low in social-status (Ollendick & Benoit, 2012;Brumariu, et al, 2013), and models of others as rejecting. These activate evolutionary behaviours of submission to and avoidance of others, which induce and reinforce anxiety in social domains (Weisman, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies suggested a link between attachment disorganization and anxiety. Pioneer studies reported a high prevalence of unresolved attachment states of mind in adult patients with anxiety disorders [15, 36], while a recent study on late adolescents found that the presence of anxiety disorders and comorbid conditions was associated with higher levels of attachment disorganization [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Securely attached children are more cooperative, better liked by peers, and form more supportive friendships than insecurely attached children (Booth‐LaForce & Kerns, ; Schneider, Atkinson, & Tardif, ). Peer relationships are also related to anxiety in that more anxious children perceive themselves to be less competent with peers, are more likely to be victimized by peers, and have more difficulties in friendships and romantic relationships (Brumariu et al., ; Kingery, Erdley, Marshall, Whitaker, & Reuter, ). Consistent with the idea that peer relationships play a role in explaining associations between attachment and anxiety, in two studies, children securely attached in the first 3 years were more competent with peers in middle childhood, which in turn accounted for why they experienced less anxiety in late childhood or adolescence (Bosquet & Egeland, ; Brumariu & Kerns, ).…”
Section: Why Is Attachment Related To Anxiety?mentioning
confidence: 99%